2007
DOI: 10.1038/sj.cr.7310137
|View full text |Cite
|
Sign up to set email alerts
|

Niche regulation of corneal epithelial stem cells at the limbus

Abstract: Among all adult somatic stem cells, those of the corneal epithelium are unique in their exclusive location in a defined limbal structure termed Palisades of Vogt. As a result, surgical engraftment of limbal epithelial stem cells with or without ex vivo expansion has long been practiced to restore sights in patients inflicted with limbal stem cell deficiency. Nevertheless, compared to other stem cell examples, relatively little is known about the limbal niche, which is believed to play a pivotal role in regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
203
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(219 citation statements)
references
References 115 publications
(140 reference statements)
3
203
0
9
Order By: Relevance
“…The reason for this debilitating condition has been attributed to malfunctioning of the corneal epithelial stem cells visualized by a progressive deterioration of the stem cell environment, the palisades of Vogt [2][3][4][5]. The break-down of the stem cell niche triggers conjunctivalisation and eventually opacification of the cornea [6].…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this debilitating condition has been attributed to malfunctioning of the corneal epithelial stem cells visualized by a progressive deterioration of the stem cell environment, the palisades of Vogt [2][3][4][5]. The break-down of the stem cell niche triggers conjunctivalisation and eventually opacification of the cornea [6].…”
Section: Introductionmentioning
confidence: 99%
“…Corneal epithelial stem cells are regulated by their own microenvironment, including cell-cell and cell-extracellular matrix (ECM), known as the 'stem-cell niche'. [15][16][17] Previous study demonstrated that some growth factors and morphogenetic factors bind directly to particular ECMs and regulate cell proliferation and differentiation. 18 Moreover, the variations in basement membranes are known to depend on the tissue.…”
mentioning
confidence: 99%
“…Chronic inflammation in the limbus, the common denominator of limbal stem cell deficiency, had been confirmed to threaten the well-being of transplanted limbal autograft. [24][25][26] Long-term ICs infiltration in the limbus may result in loss of LSCs and dysfunction of remaining LSCs, then leads to delay of corneal epithelial recovery. In eyes classified as grade I and II injury, DCs infiltration in the limbus was found.…”
Section: Eyementioning
confidence: 99%